Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
y = x² + 4x - 4
x² + 4x - 4 = 0
x = -(4) +/- √((4)² - 4(1)(-4))
2(1)
x = -4 +/- √(16 + 16)
2
x = -4 +/- √(32)
2
x = -4 +/- 4√(2)
2
x = -2 + 2√(2)
x = -2 + 2√(2) x = -2 - 2√(2)
y = x² + 4x - 4
y = (-2 + 2√(2))² + 4(-2 + 2√(2)) - 4
y = (4 - 4√(2) + 8) + (-8 + 8√(2)) - 4
y = 4 + 8 - 8 - 4 - 4√(2) + 8√(2)
y = 4√(2)
(x, y) = (-2 + 2√(2), 4√(2))
or
y = x² + 4x - 4
y = (-2 - 2√(2))² + 4(-2 - 2√(2)) - 4
y = (4 + 4√(2) + 8) + (-8 - 8√(2)) - 4
y = 4 + 8 - 8 - 4 + 4√(2) - 8√(2)
y = -4√(2)
(x, y) = (-2 - 2√(2), -4√(2))
x² + 4x - 4 = 0
x = -(4) +/- √((4)² - 4(1)(-4))
2(1)
x = -4 +/- √(16 + 16)
2
x = -4 +/- √(32)
2
x = -4 +/- 4√(2)
2
x = -2 + 2√(2)
x = -2 + 2√(2) x = -2 - 2√(2)
y = x² + 4x - 4
y = (-2 + 2√(2))² + 4(-2 + 2√(2)) - 4
y = (4 - 4√(2) + 8) + (-8 + 8√(2)) - 4
y = 4 + 8 - 8 - 4 - 4√(2) + 8√(2)
y = 4√(2)
(x, y) = (-2 + 2√(2), 4√(2))
or
y = x² + 4x - 4
y = (-2 - 2√(2))² + 4(-2 - 2√(2)) - 4
y = (4 + 4√(2) + 8) + (-8 - 8√(2)) - 4
y = 4 + 8 - 8 - 4 + 4√(2) - 8√(2)
y = -4√(2)
(x, y) = (-2 - 2√(2), -4√(2))
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.